Exploring preferences and sustainable attitudes of Airbnb green users in the review comments and ratings: a text mining approach. Issue 7 (12th April 2021) - Serrano, Laura; Ariza-Montes, Antonio; Nader, Martín; Sianes, Antonio; Law, Rob
Abstract: The sharing economy platforms for accommodation have emerged as a disruptive model that has revolutionized the tourist lodging sector and modified tourist consumption patterns. Airbnb is the paradigm of this business model, with approximately 300 million users and more than 7 million listings worldwide. However, studies that have attempted to explore the consumer experiences of green Airbnb users are still scarce, especially those using big data approaches. The present study explores the preferences and attitudes of green Airbnb users by analyzing the online review published in Inside Airbnb using text mining and sentiment analysis. Findings reveal six latent aspects among which the "sustainability" predominates in the online opinions of green Airbnb users, situating sustainability in relation to the most positive emotion of the Plutchik model. Moreover, the results of the analysis suggest a positivity bias in the online reviews of green Airbnb users. Managerial implications for sustainability, consumer behavior management, and marketing fields are discussed.